2019
DOI: 10.1136/bcr-2018-226398
|View full text |Cite
|
Sign up to set email alerts
|

Adult with intestinal malrotation and colocolic intussusception: an unusual combo

Abstract: Intestinal malrotation is a congenital anomaly that results from an abnormality in the rotation and fixation of the gut as it returns to the abdominal cavity during development. Intussusception is a condition characterised by telescoping of one segment of the bowel into another segment. The combination of malrotation and intussusception is frequently a cause of intestinal obstruction in the paediatric age group. The coexistence of these two conditions is termed as Waugh syndrome and is uncommon in adults. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
(22 reference statements)
0
6
0
1
Order By: Relevance
“…Intestinal malrotation is any deviation from the normal embryonic 270° counterclockwise rotation of the midgut and is classified into three types according to the embryonic stage in which the process of rotation was interrupted. There are three types of malrotation: type 1 is non-rotation, type 2 includes only small bowel malrotation and type 3 is defined as malrotation of the duodenum and cecum 2. The patient in our report had type 1 or non-rotational malrotation as evidenced by his rightward duodenum and the leftward position of his colon.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Intestinal malrotation is any deviation from the normal embryonic 270° counterclockwise rotation of the midgut and is classified into three types according to the embryonic stage in which the process of rotation was interrupted. There are three types of malrotation: type 1 is non-rotation, type 2 includes only small bowel malrotation and type 3 is defined as malrotation of the duodenum and cecum 2. The patient in our report had type 1 or non-rotational malrotation as evidenced by his rightward duodenum and the leftward position of his colon.…”
Section: Discussionmentioning
confidence: 62%
“…Ultrasound can be used to identify the reversal of normal anatomic positioning of the SMA and superior mesenteric vein (SMV) and the bird-beak appearance of the duodenum indicating an obstruction but carries a high false negative rate of up to 21% 4. Characteristic imaging findings are an anterior and leftward SMV in relation to the SMA (figure 4), a hypoplastic uncinate process of the pancreas and abnormal position of the duodenal-jejunal flexure with small bowel loops on the right and leftward position of the colon 2. Despite the diagnostic imaging findings, acute and complex cases must be confirmed with surgical exploration 4.…”
Section: Discussionmentioning
confidence: 99%
“…Type 1 is the most common, found in 2 per 1000 cases of upper gastrointestinal contrast studies 7. Previous studies have reported a lower incidence of type 2 malrotation than the other types, probably because it is unfamiliar to clinicians, includes several subtypes and is less apparent on radiological and intraoperative findings than type 1 or type 3 2 5 8. When found along with colonic cancer, studies have reported either type 1 or type 3 malrotation 9 10…”
Section: Discussionmentioning
confidence: 99%
“…Brereton et al conducted a prospective study where they identified intestinal malrotation-associated intussusceptions in 15 patients, coining the term "Waugh's syndrome" after George E. Waugh [ 7 ]. Although intussusception causes only 5% of cases of intestinal obstruction in adults, about 80 to 90% are secondary to underlying pathologies [ 8 ]. Adults, unlike children and infants present with intussusception, generally have a lead point.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant or benign neoplasms account for around 65% of the adult intussusceptions [ 8 ]. A moveable right colon by a long meso-colon results from an intestinal malrotation.…”
Section: Discussionmentioning
confidence: 99%